Persistent bacteremia caused by Ralstonia pickettii and Microbacterium: a case report - Jinwen Wang; Yu Song; Siqin Liu; Xudong Jang; Lina Zhang (BMC Infectious Diseases, 2024)
Abstract Background Ralstonia pickettii is a low virulent, gram-negative bacillus that is rarely associated with human infections and may cause bacteremia. Microbacterium species are gram-positive coryneforms that are generally considered as a contaminant in Gram staining of blood cultures, especially when the time to positivity is longer than 48 h. Both these bacterial species are emerging opportunistic pathogens that may occasionally cause serious infections and even life-threatening health conditions. Case presentation Here, we report the case of a patient with bacteremia caused by both R. pickettii and Microbacterium. We advocate for providers to order rapid antibiotic susceptibility testing, since our patient’s suffered two kinds of rare pathogens with the opposite of drug sensitivity results to imipenem. Conclusions Our case present a patient suffered septic shock caused by R. pickettii and Microbacterium. Improving the antibiotic management based on the result of antimicrobial susceptibility tests is the key of successful treatment.